A critical edition of the poems of Hildebert of Le Mans - Scott, AB; Scott, AB (1960)
This edition consists of three chapters of general introduction, followed by introduction, text and notes on each of the four divisions of Hildebert’s poetry, namely the Shorter Poems, Biblical Epigrams, De Mysterio Missae and Life of St. Mary the Egyptian. Hildebert was born at Laverdin around 1056. After a period as scholasticus at Le Mans he became archdeacon in 1091. In 1096, on the death of Hoel, he was elected bishop, though not without a contest. Hildebert's first test as bishop came in 1099 with the attack on Le Mans by Helias, count of Maine, which was then held by William Rufus. Rufus, having succeeded in dislodging Helias, suspected Hildebert of complicity in the attempt, and took him with him back to England, His threat to demolish the towers of the cathedral of S. Julien were however left unfulfilled at his death. When peace returned Hildebert journeyed to Rome and the Norman lands of S. Italy (1100). This peace was broken by the fighting between Henry I of England and Louis VI, and it was at this period that Hildebert was imprisoned at Nogent-le-Rotrou. A different kind of trouble faced Hildebert some years later in the shape of the heretic Henry of Lausanne, who by his preaching succeeded in turning the people completely against their clergy. Even after his ignorance in religious matters had been shown up by Hildebert it was a long time before his influence was eradicated from the diocese. In 1125 Hildebert, now an old man, was elected archbishop of Tours. Here his refusal to install as dean and archdeacon the nominees of Louis VI, to whom Tours belonged led to the King cutting off the archiepiscopal revenues, and these were not entirely freed until 1150. Hildebert died in 1135. Continued in thesis ...